Influence of promoter polymorphisms of the TNF-α (-308G/A) and IL-6 (-174G/C) genes on therapeutic response to etanercept in rheumatoid arthritis - Jančić Ivan; Šefik-Bukilica Mirjana; Živojinović Slađana; Damjanov Nemanja; Spasovski Vesna; Kotur Nikola; Klaassen Kristel; Pavlović Sonja; Bufan Biljana; Arsenović-Ranin Nevena (Journal of Medical Biochemistry, 2015)
Background: The study was undertaken to assess the influence of functional -308G /A TNF-α (rs 1800629) and -174G/C IL-6 (rs1800795) promoter polymorphisms on the therapeutic response to etanercept, a TNF-α blocker, in patients with rheumatoid arthritis (RA). Methods: Seventy-three patients suffering from active RA were studied, at baseline and 6 and 12 months after therapy. The therapeutic response was estimated according to the European League Against Rheumatism response criteria. Patients were genotyped for -308G /A TNF-α and -174G/C IL-6 polymorphisms by the PCR-RFLP method, and the influence of genotype on etanercept response was assessed. Results: No difference in the percentage of responders (patients who had DAS28 improvement > 1.2) between patients with the TNF-α -308GG and GA and AA genotype was detected after 6 and 12 months of treatment. After 12 months of treatment the percentage of responders was significantly increased in patients with the IL-6 -174GG genotype compared with those with the GC or CC genotype (p=0.006 by Chi-square test). Evaluation of the patients according to their combined IL-6/TNF-α genotypes showed that patients with the IL-6 -174GG / TNF-α -308GG genotype were more frequent among the responders compared to those with other combined genotypes (p=0.022 by Chisquare test). More precisely, all patients with the combined IL-6 -174GG / TNF-α -308GG genotype were responders after 12 months of etanercept treatment. Conclusions: The study suggests that patients who are genetically low TNF-α and IL-6 producers are the best responders to etanercept therapy.